Stabilitas Industri Dan Agresivitas Pajak Dalam Perspektif Karakteristik Keuangan Perusahaan - Prastika, Yulia Indah; Putri, Sofie Yunida (Fakultas Ekonomi Prodi Akuntansi, 2026)
This study examines how leverage, capital intensity, and profitability influence the tax aggressiveness of non-cyclical consumer companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024. Tax aggressiveness is measured using the Cash Effective Tax Rate (CETR). A quantitative approach based on financial statement data and purposive sampling were used in this study. A sample of 46 companies was collected over a five-year period, resulting in 230 observations. Panel data regression was used as the analysis technique. The findings indicate that leverage contributes to tax aggressiveness due to the use of debt, which creates interest expenses, which can be leveraged as an instrument to reduce tax burdens. Furthermore, since the amount of tax imposed on a company is determined by its profits, profitability has a direct influence on the company's tax obligations. Capital intensity, on the other hand, does not contribute to tax aggressiveness, as the company's fixed assets are more focused on supporting operational activities. Control variables such as firm size, inventory intensity, and liquidity are used not only to increase model validity but also to demonstrate that internal company characteristics influence the relationship between the main variables in the study. This confirms that the dynamics of a company's financial condition play a crucial role in shaping an aggressive tax strategy. Keywords: Capital intensity, Leverage, Profitability, Tax Aggressiveness